2020
DOI: 10.1097/jcma.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Developing a novel meatal areolar tissue autograft for minimally invasive tympanoplasty

Abstract: Background: We developed an easy and minimally invasive method of transmeatal tympanoplasty using meatal areolar tissue (MAT) grafts to achieve less postoperative morbidity or surgical scarring. We compared the functional and anatomical results of the developed method with conventional endaural tympanoplasty with a temporalis fascia (TF) graft. Methods: In this retrospective cohort study, 58 patients (59 ears) with simple chronic otitis media who underwent type I tympanopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We are happy to learn that the authors developed a relatively novel and modified method as transmeatal approach with meatal areolar tissue (MAT) reconstruction, modified from the canonical endaural tympanoplasty and attempted to overcome the limitations of conventional tympanoplasty for the treatment of COM patients. 6 As predicted, the authors found this transmeatal approach method with a MAT graft could not only significantly reduce the severity of trauma (to avoid external skin wounds) as well as surgery-related morbidity but also had a better cosmetic result; additionally, this modified technique is easy and minimally invasive and of the most importance, the therapeutic effects are similar or not inferior to those done by other types which need more invasive procedures. 6 Based on impressive findings of the current study, it was worthy of further discussion.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…We are happy to learn that the authors developed a relatively novel and modified method as transmeatal approach with meatal areolar tissue (MAT) reconstruction, modified from the canonical endaural tympanoplasty and attempted to overcome the limitations of conventional tympanoplasty for the treatment of COM patients. 6 As predicted, the authors found this transmeatal approach method with a MAT graft could not only significantly reduce the severity of trauma (to avoid external skin wounds) as well as surgery-related morbidity but also had a better cosmetic result; additionally, this modified technique is easy and minimally invasive and of the most importance, the therapeutic effects are similar or not inferior to those done by other types which need more invasive procedures. 6 Based on impressive findings of the current study, it was worthy of further discussion.…”
mentioning
confidence: 66%
“…6 As predicted, the authors found this transmeatal approach method with a MAT graft could not only significantly reduce the severity of trauma (to avoid external skin wounds) as well as surgery-related morbidity but also had a better cosmetic result; additionally, this modified technique is easy and minimally invasive and of the most importance, the therapeutic effects are similar or not inferior to those done by other types which need more invasive procedures. 6 Based on impressive findings of the current study, it was worthy of further discussion.…”
mentioning
confidence: 66%
See 3 more Smart Citations